Generation Mechanism and Characteristic Analysis of Dual-Frequency Pseudo-Signal Interference of the Swept-Frequency Radar - Hong-Ze Zhao; Guang-Hui Wei; Xiao-Dong Pan; Xue Du; Xu-Xu Lyu (International Journal of Antennas and Propagation)
In order to master the law of the pseudo-signal interference effect of dual-frequency electromagnetic radiation in typical radar equipment, a certain type of Ku-band swept-frequency ranging radar was used as the test object to carry out single-frequency continuous wave and dual-frequency continuous wave pseudo-signal interference effect experiments. Through experiments, it is found that dual-frequency electromagnetic radiation will cause “hill” and “spike” type pseudo-signal interference to the swept-frequency radar. Based on the frequency analysis of the radar receiving circuit, the interference mechanism of the dual-frequency pseudo-signal is revealed, and the morphological characteristics and distance law of the pseudo-signal are explained. The variation law of the pseudo-signal level with interference field strength is obtained. The results show that the in-band dual-frequency nonintermodulation interference is similar to the single-frequency interference, and the only difference is that the number of pseudo-signals increases; when the interference frequency difference is about 400∼600 MHz, the out-of-band dual-frequency second-order intermodulation signal will cause “hill” type pseudo-signal interference, and the pseudo-signal distance is random; when the interference frequency difference is less than 5 MHz, both the dual-frequency second-order intermodulation signal and the third-order intermodulation signal will cause “spike” pseudo-signal interference inside and outside the radar operating frequency band; the pseudo-signal distance is fixed.